Adhesive composition for skin application and adhesive tape for skin application

The adhesive composition, featuring a tailored acrylic polymer and curing agent, addresses skin adhesion and moisture issues, ensuring effective adhesion, minimal residue, and improved comfort by enhancing permeability and resistance.

JP2025007128APending Publication Date: 2025-01-17TOYO INK MFG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023108323
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing adhesive compositions for skin application face issues such as decreased skin adhesion due to temperature changes, moisture retention leading to stuffiness and irritation, and inadequate moisture permeability, resulting in tape peeling and adhesive residue.

Method used

An adhesive composition comprising an acrylic polymer with specific monomer ratios and a curing agent, optimized for skin adhesion, moisture permeability, and water resistance, formed into a tape with a controlled gel fraction.

Benefits of technology

The adhesive composition provides excellent skin adhesion, reduces pain and residue upon removal, prevents stuffiness, and exhibits high moisture permeability and water resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007128000001
    Figure 2025007128000001
  • Figure 2025007128000002
    Figure 2025007128000002
  • Figure 2025007128000003
    Figure 2025007128000003
Patent Text Reader

Abstract

To provide an adhesive for skin application that exhibits superior skin adhesion, with reduced adhesive residue and pain upon detachment, and maintains high vapor permeability while offering superior water resistance, and an adhesive tape including the adhesive for skin application.SOLUTION: An adhesive composition for skin application comprises an acrylic polymer (A) and a curing agent (B). The acrylic polymer (A) is a copolymer of a monomer mixture. The monomer mixture being 100 mass%, comprises 30 to 83 mass% of normal butyl acrylate, 10 to 60 mass% of 2-ethylhexyl acrylate, and 6.6 to 15 mass% of a carboxyl group-containing monomer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive composition for application to the skin, and also to an adhesive tape for application to the skin having an adhesive layer formed from the adhesive composition for application to the skin. [Background technology]

[0002] Adhesives and adhesive tapes for skin application used in the medical, sports, and beauty fields need to have sufficient skin adhesion to ensure reliable adhesion to the skin surface, and in particular in winter when the adhesive layer tends to harden due to the drop in outside temperature, there is a problem of reduced skin adhesion due to reduced wettability to the skin, which can lead to the tape peeling off. At the same time, there is also a demand for minimal pain when removing the tape and minimal adhesive residue (glue residue) on the skin.

[0003] The adhesive layer of the skin adhesive tape is often made of acrylic resin or styrene elastomer, and it is important to have good adhesion to the skin, so that it is difficult to peel off. However, the adhesive layer made of the resin has a problem of low moisture permeability. The skin regulates body temperature by evaporating moisture from the surface. Therefore, the skin where the skin adhesive tape is applied has no place for moisture to escape, and moisture causes stuffiness, itching, and rashes.

[0004] Patent Document 1 discloses a medical pressure-sensitive adhesive composition containing a blend of at least two components including about 5% to about 95% by weight of a first component including at least one acrylic pressure-sensitive adhesive, and about 5% to about 95% by weight of a second component including either (a) at least one tackifier resin-containing elastomer or (b) at least one thermoplastic elastomer.

[0005] Patent Document 2 discloses an adhesive for application to the skin, which contains an acrylic adhesive containing 50 to 78% by weight of an alkoxyalkyl (meth)acrylate. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2009-62543 A [Patent Document 2] JP 2017-95598 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, although the medical pressure-sensitive adhesive composition of Patent Document 1 is an acrylic resin, it has been improved so that the skin patch tape does not lift or leave adhesive residue after being applied for an extended period of time, but the amount of adhesive residue left when the tape is removed is insufficient. In addition, the adhesive layer of the skin patch tape has low moisture permeability, which can easily cause skin rashes. The adhesive composition of Patent Document 2 contains a highly hydrophilic alkoxyalkyl (meth)acrylate as an essential component, which improves moisture permeability and suppresses skin rashes. However, the adhesive composition lacks water resistance, and there is an issue that the tape peels off due to sweat during exercise or bathing. In addition, the skin adhesion and adhesive residue are not sufficient.

[0008] The present invention has been made in consideration of the above circumstances, and aims to provide an adhesive for application to the skin that has excellent skin adhesion, leaves little glue residue or pain when peeled off, and has high moisture permeability while also having excellent water resistance, and an adhesive tape using the same. [Means for solving the problem]

[0009] The above-mentioned problems are solved by an adhesive composition for application to skin, comprising an acrylic polymer (A) and a curing agent (B), wherein the acrylic polymer (A) is a copolymer of a monomer mixture, and wherein 100 mass% of the monomer mixture contains 30.0 to 83.0 mass% of normal butyl acrylate, 10.0 to 60.0 mass% of 2-ethylhexyl acrylate, and 6.6 to 15.0 mass% of a carboxyl group-containing monomer.

[0010] Further, the above-mentioned problem is solved by the pressure-sensitive adhesive composition for application to skin, which is characterized in that the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition has a gel fraction of 0 to 50 mass %.

[0011] Further, the above-mentioned problem is solved by the pressure-sensitive adhesive composition for application to skin, characterized in that the acrylic polymer (A) has a weight-average molecular weight of 300,000 to 1,000,000.

[0012] The problem is also solved by the aforementioned pressure-sensitive adhesive composition for application to skin, which is characterized in that the carboxyl group-containing monomer constituting the acrylic polymer (A) contains methacrylic acid and further contains either acrylic acid or 2-carboxyethyl acrylate.

[0013] The above-mentioned problems are also solved by an adhesive tape for application to the skin, comprising a substrate and an adhesive layer formed from the adhesive composition for application to the skin. Effect of the Invention

[0014] According to the present invention, it is possible to provide an adhesive for application to the skin, which adheres sufficiently to the skin while causing little pain or leaving behind glue when the tape is peeled off, has high moisture permeability to prevent stuffiness, and forms an adhesive layer which also has excellent water resistance, and an adhesive tape for application to the skin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The following describes in detail the embodiments of the present invention. However, the following description is an example (representative example) of an embodiment of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention. In this specification, the pressure-sensitive adhesive tape includes a substrate and a pressure-sensitive adhesive layer formed from a cured product of the pressure-sensitive adhesive composition of the present invention.

[0016] In this specification, "acrylic polymer (A)" may be abbreviated as "polymer (A)". In addition, in this specification, a numerical range specified using "~" includes the numerical values ​​before and after "~" as the lower and upper limit values. Unless otherwise noted, the various components appearing in this specification may be used independently as a single type or as a combination of two or more types.

[0017] In this specification, unless otherwise specified, "molecular weight" refers to weight average molecular weight (Mw). Note that "Mw" is a weight average molecular weight calculated in terms of polystyrene obtained by gel permeation chromatography (GPC).

[0018] <Acrylic polymer (A)> The acrylic polymer (A) is a copolymer of a monomer mixture containing 30.0 to 83.0 mass% of normal butyl acrylate, 10.0 to 60.0 mass% of 2-ethylhexyl acrylate, and 6.6 to 15.0 mass% of a carboxyl group-containing monomer, based on 100 mass% of the monomer mixture.

[0019] The content of normal butyl acrylate in 100% by mass of the monomer mixture constituting the polymer (A) is 30.0 to 83.0% by mass, and preferably 40.0 to 70.0% by mass. By making it 30.0% by mass or more, it is possible to improve moisture permeability and adhesive residue, and by making it 83.0% by mass or less, it is possible to improve skin adhesion and reduce pain during peeling.

[0020] The content of 2-ethylhexyl acrylate in 100% by mass of the monomer mixture constituting the polymer (A) is 10.0 to 60.0% by mass, and preferably 15.0 to 50.0% by mass. By making it 10.0% by mass or more, it is possible to achieve both excellent skin adhesive strength and reduced pain during peeling, and by making it 60.0% by mass or less, it is possible to improve moisture permeability.

[0021] The content of the carboxyl group-containing monomer in the 100% by mass of the monomer mixture constituting the polymer (A) is 6.6 to 15.0% by mass, and preferably 7.5 to 13.0% by mass. By making it 6.6% by mass or more, it is possible to improve the cohesive strength and reduce adhesive residue, and by making it 15.0% by mass or less, it is possible to improve the skin adhesive strength. Examples of the carboxyl group-containing monomer include (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, 2-succinoyloxyethyl (meth)acrylate, maleic acid, monoethylmaleic acid, itaconic acid, citraconic acid, and fumaric acid. Among these, (meth)acrylic acid and 2-carboxyethyl (meth)acrylate are preferred in terms of copolymerizability, and it is more preferred to use methacrylic acid in combination with acrylic acid or 2-carboxyethyl acrylate. If the content of methacrylic acid in the monomer mixture is C and the total content of acrylic acid and / or 2-carboxyethyl acrylate is D, the ratio (C / D) is particularly preferably C / D=0.1 to 5. The inclusion of methacrylic acid improves the cohesive strength and reduces adhesive residue, while the inclusion of acrylic acid or 2-carboxyethyl acrylate improves reactivity with the curing agent (B) and enables excellent curing properties to be exhibited.

[0022] The acrylic polymer (A) may contain monomers other than the above monomers as constituent monomers.

[0023] Other monomers include methyl (meth)acrylate, ethyl (meth)acrylate, normal propyl (meth)acrylate, isopropyl (meth)acrylate, normal butyl methacrylate, isobutyl methacrylate, tertiary butyl methacrylate, normal pentyl methacrylate, normal hexyl methacrylate, 2-ethyl butyl methacrylate, 2-methyl pentyl methacrylate, 1,3-dimethyl butyl methacrylate, normal octyl methacrylate, and 2-ethyl hexyl methacrylate. (meth)acrylic acid alkyl ester monomers such as 6-methylheptyl methacrylate, normal nonyl methacrylate, 6-methyloctyl methacrylate, normal decyl methacrylate, normal methylnonyl methacrylate, normal undecyl methacrylate, lauryl methacrylate, 7-methyloctyl methacrylate, 8-methylnonyl methacrylate, 8-methyldecyl methacrylate, 9-methyldecyl methacrylate, 9-methylundecyl methacrylate, and 10-methylundecyl methacrylate; alkoxyalkyl (meth)acrylates such as 2-methoxymethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxymethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate; Acidic group-containing ethylenic monomers such as paravinylbenzenesulfonic acid, 2-acrylamidopropanesulfonic acid, etc.; Aromatic-containing monomers such as styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, m-methylstyrene, vinylnaphthalene, benzyl acrylate, benzyl methacrylate, phenoxyethyl acrylate, phenoxyethyl methacrylate, phenoxydiethylene glycol acrylate, phenoxydiethylene glycol methacrylate, phenoxytetraethylene glycol acrylate, phenoxytetraethylene glycol methacrylate, phenoxyhexaethylene glycol acrylate, phenoxyhexaethylene glycol methacrylate, phenyl acrylate, and phenyl methacrylate; Alicyclic alkyl group-containing ethylenically unsaturated monomers, such as cyclohexyl (meth)acrylate and isobornyl (meth)acrylate; (Meth)acrylamide, N-methoxymethyl-(meth)acrylamide, N-ethoxymethyl-(meth)acrylamide, N-propoxymethyl-(meth)acrylamide, N-butoxymethyl-(meth)acrylamide, N-pentoxymethyl-(meth)acrylamide, N,N-di(methoxymethyl)acrylamide, N-ethoxymethyl-N-methoxymethylmethacrylamide, N,N-di(ethoxymethyl)acrylamide, N-ethoxymethyl-N-propoxymethylmethacrylamide, N,N-di(propoxymethyl)acrylamide Amide group-containing ethylenically unsaturated monomers such as acrylamide, N-butoxymethyl-N-(propoxymethyl)methacrylamide, N,N-di(butoxymethyl)acrylamide, N-butoxymethyl-N-(methoxymethyl)methacrylamide, N,N-di(pentoxymethyl)acrylamide, N-methoxymethyl-N-(pentoxymethyl)methacrylamide, N,N-dimethylaminopropylacrylamide, N,N-diethylaminopropylacrylamide, N,N-dimethylacrylamide, and N,N-diethylacrylamide; Hydroxyl group-containing ethylenically unsaturated monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycerol mono(meth)acrylate, 4-hydroxyvinylbenzene, 1-ethynyl-1-cyclohexanol, and allyl alcohol; Allyl (meth)acrylate, 1-methylallyl (meth)acrylate, 2-methylallyl (meth)acrylate, 1-butenyl (meth)acrylate, 2-butenyl (meth)acrylate, 3-butenyl (meth)acrylate, 1,3-methyl-3-butenyl (meth)acrylate, 2-chloroallyl (meth)acrylate, 3-chloroallyl (meth)acrylate, o-allylphenyl (meth)acrylate, 2-(allyloxy)ethyl (meth)acrylate, allyl lactyl (meth)acrylate, citronellyl (meth)acrylate, geranyl (meth)acrylate, rosinyl (meth)acrylate, cinnamyl (meth)acrylate, diallyl maleate, diallyl itaconic acid, vinyl (meth)acrylate, vinyl crotonate ethylenically unsaturated monomers having two or more ethylenically unsaturated groups, such as vinyl oleate, vinyl linoleate, 2-(2'-vinyloxyethoxy)ethyl (meth)acrylate, ethylene glycol di(meth)acrylate, triethylene glycol (meth)acrylate, tetraethylene glycol (meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, 1,1,1-trishydroxymethylethane diacrylate, 1,1,1-trishydroxymethylethane triacrylate, 1,1,1-trishydroxymethylpropane triacrylate, divinylbenzene, divinyl adipate, diallyl isophthalate, diallyl phthalate, and diallyl maleate; Epoxy group-containing ethylenically unsaturated monomers such as glycidyl (meth)acrylate and 3,4-epoxycyclohexyl (meth)acrylate; alkoxysilyl group-containing ethylenically unsaturated monomers such as γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-methacryloxypropyltributoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-acryloxypropyltrimethoxysilane, γ-acryloxypropyltriethoxysilane, γ-acryloxypropylmethyldimethoxysilane, γ-methacryloxymethyltrimethoxysilane, γ-acryloxymethyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltributoxysilane, and vinylmethyldimethoxysilane; and the like. The other monomers can be used alone or in combination of two or more. The content of other monomers is preferably 20% by mass or less in 100% by mass of the monomer mixture. In addition, when a (meth)acrylic acid alkyl ester having an alkyl chain with 1 to 2 carbon atoms or a hydroxyl group-containing ethylenically unsaturated monomer is used, the skin adhesive strength decreases, so the content of the (meth)acrylic acid alkyl ester having an alkyl chain with 1 to 2 carbon atoms or the hydroxyl group-containing ethylenically unsaturated monomer is preferably 10 mass% or less in 100 mass% of the monomer mixture. In addition, the use of an alkoxyalkyl (meth)acrylate can improve moisture permeability, but adding too much will reduce skin adhesion and water resistance, so the content of the alkoxyalkyl (meth)acrylate is preferably 10 mass% or less in 100 mass% of the monomer mixture.

[0024] The acrylic polymer (A) preferably has a weight average molecular weight of 300,000 to 1,000,000, and more preferably 350,000 to 700,000. When it is 300,000 or more, adhesive residue can be reduced, and when it is 1,000,000 or less, the adhesiveness on the skin is good.

[0025] The acrylic polymer (A) can be produced by a known method, but is preferably produced by solution polymerization. In the solution polymerization, it is preferable to use a solvent such as methyl acetate, ethyl acetate, methyl ethyl ketone, toluene, or acetone.

[0026] Specifically, the solvent and raw monomers are charged into a reaction vessel in the ratio described above, a polymerization initiator is added under an inert gas atmosphere such as nitrogen gas, and the mixture is heated to a reaction temperature of about 50 to 90°C and polymerized for 4 to 20 hours.

[0027] Examples of the polymerization initiator include an azo-based initiator and a peroxide-based initiator. These polymerization initiators are usually used in an amount ranging from 0.01 to 5 parts by mass relative to 100 parts by mass of the monomer mixture. In addition, a chain transfer agent, raw material monomers, and a solvent may be appropriately added during the polymerization reaction.

[0028] Under the above conditions, the weight average molecular weight of the resulting copolymer can be adjusted according to known techniques by adjusting reaction conditions such as the type and amount of the solvent used, the type and amount of the polymerization initiator, the reaction time, the reaction temperature, etc.

[0029] <Hardening agent B>

[0030] In the present invention, the curing agent B is preferably at least one selected from the group consisting of an isocyanate compound, an epoxy compound, an aziridine compound, a metal chelate, and an amine compound, and more preferably an isocyanate compound or a metal chelate. By using an isocyanate compound or a metal chelate, excellent curability and skin adhesiveness can be achieved.

[0031] Examples of the isocyanate compound include adducts of diisocyanates such as tolylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, tetramethylxylylene diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, and polymethylene polyphenyl isocyanate with polyol compounds such as trimethylolpropane, as well as biuret forms and isocyanurates thereof, and adducts of the above diisocyanates with any one of polyols such as polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, and polyisoprene polyols, and other compounds having three or more isocyanate groups in the molecule; Examples of the diisocyanates include tolylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, tetramethyl xylylene diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, and polymethylene polyphenyl isocyanate, as well as compounds having two isocyanate groups in the molecule, such as allophanate bodies of hexamethylene diisocyanate; and the like. Among these, the trimethylolpropane adduct of tolylene diisocyanate is preferred because it can easily adjust the adhesive properties. The number of isocyanate groups is the average number.

[0032] Examples of epoxy compounds include bisphenol A-epichlorohydrin type epoxy resins, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, diglycidylaniline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidylaminophenylmethane.

[0033] Examples of the aziridine compound include N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxite), N,N'-toluene-2,4-bis(1-aziridinecarboxite), bisisophthaloyl-1-(2-methylaziridine), tri-1-aziridinylphosphine oxide, N,N'-hexamethylene-1,6-bis(1-aziridinecarboxite), 2,2'-bishydroxymethylbutanol-tris[3-(1-aziridinyl)propionate], trimethylolpropane tri-β-aziridinylpropionate, tetramethylolmethane tri-β-aziridinylpropionate, and tris-2,4,6-(1-aziridinyl)-1,3,5-triazine.

[0034] Examples of the metal chelate include coordination compounds of polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium and zirconium with acetylacetone or ethyl acetoacetate.

[0035] Examples of the amine compound include hexamethylenediamine, triethyldiamine, polyethyleneimine, hexamethylenetetramine, diethylenetriamine, triethyltetramine, isophoronediamine, amino resins, and methylene resins.

[0036] The curing agent (B) is preferably contained in an amount of 0.01 to 6 parts by mass, more preferably 0.1 to 4 parts by mass, based on 100 parts by mass of the acrylic polymer (A). When the curing agent (B) is contained in an amount of 0.01 to 6 parts by mass, it becomes easy to balance the cohesive strength and adhesive strength of the pressure-sensitive adhesive layer.

[0037] <Other optional ingredients> The pressure-sensitive adhesive composition of the present invention may contain other optional components as necessary within the range that does not impair the effects of the present invention. The optional components include resins, fillers, metal powders, pigments, foils, softeners, conductive agents, antioxidants, UV absorbers, light stabilizers, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, defoamers, tackifier resins, hydrophilic plasticizers, and lubricants.

[0038] Fillers include talc, calcium carbonate, and titanium oxide.

[0039] Examples of the antioxidant include radical chain inhibitors such as phenol-based antioxidants; and peroxide decomposers such as sulfur-based antioxidants and phosphorus-based antioxidants. Various additives can be added to the adhesive of the present invention as desired. Examples of such additives include antibacterial agents, moisturizing agents, vitamins, fragrances, etc. These are blended in effective amounts as necessary.

[0040] Examples of tackifier resins include rosin-based resins having a hydroxyl group, such as rosin ester, polymerized rosin, hydrogenated rosin, disproportionated rosin, maleic acid modified rosin, fumaric acid modified rosin, and rosin phenolic resin; and terpene-based resins, such as α-pinene resin, β-pinene resin, dipentene resin, aromatic modified terpene resin, hydrogenated terpene resin, terpene phenolic resin, acid modified terpene resin, and styrenated terpene resin. By including a tackifier resin, excellent skin adhesion can be achieved. However, if a large amount is added, it can lead to increased skin irritation. Therefore, the amount added is preferably 0 to 10 parts by mass per 100 parts by mass of the acrylic polymer (A).

[0041] Examples of hydrophilic plasticizers include polyhydric alcohols such as ethylene glycol, 1,4-butanediol, glycerin, and propylene glycol; polyoxyalkylene compounds having an amino group such as polyoxypropylene diamine, methoxypoly(oxyethylene / oxypropylene)-2-propylamine, and trimethylolpropane poly(oxypropylene)triamine; and polyoxyalkylene compounds not having an amino group such as polyethylene glycol or polypropylene glycol having a number average molecular weight of 200 to 10,000. By including a hydrophilic plasticizer, it is possible to exhibit excellent moisture permeability. However, if a large amount is added, this leads to deterioration of water resistance and skin adhesion, so the amount added is preferably 0 to 10 parts by mass per 100 parts by mass of the acrylic polymer (A).

[0042] <Adhesive tape for application to the skin> The tape for application to skin of the present invention comprises a substrate and an adhesive layer formed from an adhesive composition for application to skin. Examples of the substrate include plastic films (polyethylene, polypropylene, ethylene / vinyl acetate copolymer, polystyrene, polyester, polyvinyl chloride, polyvinylidene chloride, polyurethane, polyamide, etc.), porous substrates (woven fabric, knitted fabric, nonwoven fabric, paper), metal foils, and laminates thereof. The substrate may be stretchable or non-stretchable. Nonwoven fabric, woven fabric, knitted fabric, etc. are preferred as the support, since they provide an adhesive tape with high moisture permeability. The thickness of the substrate is not particularly limited, but is usually 10 to 1000 μm, and from the viewpoint of combining flexibility and strength, it is preferably 20 to 500 μm.

[0043] The adhesive layer is generally formed by coating the adhesive composition on a substrate. Alternatively, the adhesive composition is coated on a release sheet to form an adhesive layer, which is then transferred to the substrate. In addition, a release sheet is usually attached to the surface of the adhesive layer that is not in contact with the substrate for storage.

[0044] The adhesive composition can be applied by known coating methods such as spin coating, spray coating, bar coating, knife coating, roll coating, roll knife coating, blade coating, die coating, and gravure coating. It is also preferable to carry out a drying step during application. Known devices such as a hot air oven, an electric oven, and an infrared heater can be used for the drying step. The thickness of the adhesive layer is usually 10 to 100 g / m2 in order to achieve both adhesion and peelability. 2 Approximately 20 to 50 g / m 2 is more preferred.

[0045] The gel fraction of the adhesive layer formed from the adhesive composition for skin application is preferably 0 to 50% by mass. By setting the gel fraction to 50% by mass or less, it is possible to improve the skin adhesion while reducing adhesive residue.

[0046] The above gel fraction is a value calculated by the following formula (1) after cutting an adhesive tape having an adhesive layer to a predetermined size, attaching it to a SUS200 mesh (mesh size: 0.077 mm, wire diameter: 0.05 mm), immersing it in ethyl acetate, extracting it at 50° C. for 24 hours, and drying it at 100° C. for 30 minutes. The term "gel fraction of an adhesive layer formed from an adhesive composition for application to skin" used herein means the gel fraction of an adhesive tape after curing, which will be described later. Equation (1) Gel fraction (mass%) = (G2 / G1) x 100 G1: Mass of the adhesive layer before extraction with ethyl acetate G2: Mass of adhesive layer after extraction with ethyl acetate and drying

[0047] The adhesive tape for application to the skin of the present invention can be used in the medical, sports, and beauty fields, and can be particularly used by adhering it to the skin for medical purposes such as first aid bandages, bandages, large bandages with pads, and dressing materials. EXAMPLES

[0048] Hereinafter, specific examples of the present invention will be described together with comparative examples, but the present invention is not limited to the examples. In the examples, "parts" means "parts by mass" and "%" means "% by mass". The blending ratios are expressed in terms of solid content except for the solvent.

[0049] The materials used are as follows: BA: normal butyl acrylate 2EHA: 2-Ethylhexyl acrylate AA: Acrylic acid MAA: Methacrylic acid β-CEA: 2-carboxyethyl acrylate HEA: Hydroxyethyl acrylate MTA: 2-Methoxyethyl acrylate MA: Methyl acrylate MMA: Methyl methacrylate

[0050] <Hardening agent (B)> Aluminum chelate A: Aluminum tris(acetylacetonate), manufactured by Kawaken Fine Chemicals Co., Ltd. Desmodur L75: tolylene diisocyanate-trimethylolpropane, manufactured by Covestro Urethanes, NCO% 17.3%. <Tackifier> D-125: Pencel D-125, manufactured by Arakawa Chemical Industries, Ltd., polymerized rosin ester <Hydrophilic plasticizer> PEG400: Polyethylene glycol, average molecular weight 400

[0051] (Synthesis Example 1) In a four-neck flask equipped with a stirrer, reflux condenser, nitrogen inlet tube, thermometer, and dropping funnel, 17 parts of normal butyl acrylate, 28.5 parts of 2-ethylhexyl acrylate, 0.5 parts of 2-hydroxyethyl acrylate, 4 parts of methacrylic acid, 69 parts of ethyl acetate, and 0.1 parts of Perbutyl O as a polymerization initiator were charged, and the temperature was raised to 80°C while introducing nitrogen gas. In the dropping funnel, 17 parts of normal butyl acrylate, 28.5 parts of 2-ethylhexyl acrylate, 0.5 parts of 2-hydroxyethyl acrylate, 4 parts of methacrylic acid, 69 parts of ethyl acetate, and 0.1 parts of Perbutyl O as a polymerization initiator were charged, and the mixture was dropped to perform a polymerization reaction at 80°C for 7 hours under a nitrogen atmosphere. After the reaction was completed, 48 parts of ethyl acetate was added to dilute the mixture, and an acrylic polymer with a non-volatile content of 35% and a weight average molecular weight of 510,000 was obtained.

[0052] <Weight average molecular weight (Mw)> Mw was measured under the following conditions: Mw was determined by a calibration curve method using polystyrene with a known weight average molecular weight as the standard substance. Device name: Shimadzu Corporation, LC-GPC system "Prominence" Column: Two Tosoh TSKgel α-M columns connected in series. Mobile phase solvent: Tetrahydrofuran Flow rate: 1.0ml / min Column temperature: 40℃

[0053] (Synthesis Examples 2 to 23) An acrylic polymer was obtained in the same manner as in Synthesis Example 1, except that the materials and compositions were changed to those shown in Table 1. The weight average molecular weight was adjusted by changing the amount of the polymerization initiator. The numerical values ​​in the table represent parts unless otherwise specified, and blanks represent empty values.

[0054] [Table 1]

[0055] Example 1 <Preparation of Adhesive Composition> To 100 parts of the nonvolatile content of the obtained acrylic polymer, 0.4 parts of aluminum chelate A was added as a curing agent in terms of nonvolatile content, and the mixture was stirred to obtain a pressure-sensitive adhesive composition.

[0056] <Curability> The adhesive composition obtained above was applied to a 38 μm thick polyester separator (trade name "Superstic" SP-PET38, manufactured by Lintec Corporation) so that the thickness after drying was 25 μm, and dried in a hot air oven at 110° C. for 2 minutes. Next, a 50 μm thick polyethylene terephthalate (PET) film ("Lumirror T-60" manufactured by Toray Industries, Inc.) was attached to the coated surface, and a sample was aged for 1 week in an atmosphere of 23° C.-50% RH (1-week aged adhesive tape), and a sample was further aged at 50° C. for 6 days (cured adhesive tape). The gel fraction of each sample was measured, and the rate of change in gel fraction was calculated based on the following formula to evaluate the curability. Formula: Gel fraction change rate (%) = {(H2-H1) / H2} x 100 In the above formula, the symbols represent the following parameters. H1: Gel fraction of the adhesive layer of the 1-week curing adhesive tape, H2: Gel fraction of the adhesive layer of the cured adhesive tape (gel fraction of the cured product). [Evaluation Criteria] ○: Gel fraction change rate is 20% or less, good △: Gel fraction change rate is more than 20% and less than 60%, usable ×: Gel fraction change rate is 60% or more, not practical <Skin irritation> The adhesive tape used in the above initial hardening test was applied to a 30 cm 2 The test pieces were applied to the upper arms of 10 adult male and female test subjects, and the condition of the skin surface was visually observed after 12 hours. 〇: All patients had no erythema and were in good condition. △: 1 to 2 people had erythema, but usable. ×: 3 to 10 people had erythema, not suitable for practical use. <Making adhesive tape> Adhesive tapes were prepared according to the method described below, and their properties (skin adhesion, pain when peeling, adhesive residue, water resistance, and moisture permeability) were evaluated. The adhesive composition obtained above was applied to a 38 μm thick polyester separator (product name "Superstic" SP-PET38, manufactured by Lintec Corporation) so that the thickness after drying would be 25 μm, and then dried in a hot air oven at 110° C. for 2 minutes. After drying, the adhesive composition was laminated onto a polyester nonwoven fabric substrate (product name "Sontara #8010", manufactured by Jacob-Holm) and further aged at 50° C. for 6 days to obtain an adhesive tape for various evaluations.

[0057] <Skin adhesion, pain when peeling, glue residue> In an atmosphere of 23℃-50%RH, the inside of the forearm of 10 adult men and women was lightly wiped with ethanol, air-dried for 10 minutes, and then a test piece of the above adhesive tape measuring 12mm wide x 40mm long was applied to the surface. After 36 hours of application, the skin was observed for peeling, pain when peeling, and whether or not there was any adhesive residue (glue residue) on the skin after peeling, and evaluated according to the following criteria.

[0058] Skin adhesion: The adhesive state of the adhesive tape 36 hours after application was evaluated according to the following criteria. [Evaluation Criteria] ○: 9 to 10 people found that the coating was well attached over the entire surface of the test piece, which was good. △: 4 to 8 people found that the coating was well adhered over the entire surface of the test piece, and the test piece was usable. ×: 0 to 3 people had good adhesion over the entire surface of the test piece, not practical.

[0059] Pain during peeling: The test piece was peeled off at a peeling speed of 300 mm / min, and the pain felt at that time was evaluated according to the following criteria. [Evaluation Criteria] ○: 6 to 10 people did not feel pain, good. △: 3 to 5 people did not feel pain, practical. ×: 0 to 2 people did not feel pain, not practical.

[0060] Adhesive residue: The test piece was peeled off at a peeling speed of 300 mm / min, and the degree of adhesive remaining on the skin after peeling was evaluated according to the following criteria. [Evaluation Criteria] ○: No glue residue was observed in 9 to 10 subjects, good. △: No glue residue was observed by 6 to 8 people, usable. ×: No glue residue was observed in 0 to 5 subjects. Not practical.

[0061] <Water resistance> A test piece of the above adhesive tape measuring 12 mm wide x 40 mm long was applied to the inside of the forearm of a total of 10 adult men and women. Immediately after application, the subjects took a bath for 30 minutes or more, which included washing the body. After bathing, the subjects were observed to see if the tape had peeled off, and the results were evaluated according to the following criteria. ○: 9 to 10 people found that the coating was well attached over the entire surface of the test piece, which was good. △: 5 to 8 people found that the coating was well adhered over the entire surface of the test piece, and the test piece was usable. ×: 0 to 4 people had good adhesion over the entire surface of the test piece, not practical. <Moisture permeability> A test was conducted in accordance with JIS L1099. 42 g of pure water at 40°C was placed in a cylindrical weighing container with a diameter of 70 mm, and the adhesive tape was fixed as a lid to the weighing container so that the adhesive-coated surface of the test piece, which had been peeled off to form a substrate / adhesive layer, was facing down, and the container was sealed. This was left to stand for 1 hour in a thermo-hygrostat at 40°C and a relative humidity of 20%RH, and the amount of moisture permeated per square meter area and 24 hours was calculated from the weight loss of the weighing container, and the moisture permeability (unit: g / m2) of the adhesive tape was calculated. 2 -24h). ○: 1000g / m 2 ·24 hours or more (good) △:700g / m 2 ·More than 24 hours, 1000g / m 2 Less than 24 hours (available) ×:700g / m 2 Less than 24 hours (bad)

[0062] (Examples 2 to 25, Comparative Examples 1 to 8) Except for changing the materials, compositions, and amounts shown in Table 2, pressure-sensitive adhesive compositions and pressure-sensitive adhesive tapes were produced and measurements and evaluations were carried out in the same manner as in Example 1. Unless otherwise specified, the values ​​in the table represent parts, and blanks represent values ​​not used.

[0063] [Evaluation Results] The evaluation results are shown in Table 3.

[0064] In Examples 1 to 25, which are adhesive tapes for application to the skin using an adhesive for application to the skin containing an acrylic polymer (A) and a curing agent (B), the evaluation results were acceptable or good for all evaluation items.

[0065] In particular, in Examples 8, 9, 18, 20, and 21, which are adhesive tapes for application to the skin using polymer (A) (Synthesis Examples 8 and 9) having a BA and 2EHA content within the preferred range, and containing MAA and AA or β-CEA and a weight-average molecular weight within the preferred range, and further having a gel fraction within the preferred range, the evaluation results were good in all evaluation items.

[0066] On the other hand, none of the pressure-sensitive adhesive tapes of Comparative Examples 1 to 8, which did not use the acrylic polymer (A), cleared all the evaluation criteria.

[0067] [Table 2]

[0068] [Table 3]

Claims

1. Contains an acrylic polymer (A) and a curing agent (B), The acrylic polymer (A) is a copolymer of a monomer mixture, A pressure-sensitive adhesive composition for application to the skin, comprising, relative to 100% by mass of a monomer mixture, 30.0 to 83.0% by mass of normal butyl acrylate, 10.0 to 60.0% by mass of 2-ethylhexyl acrylate, and 6.6 to 15.0% by mass of a carboxyl group-containing monomer.

2. 2. The adhesive composition for application to skin according to claim 1, wherein the adhesive layer formed from the adhesive composition has a gel fraction of 0 to 50% by mass.

3. 2. The adhesive composition for application to the skin according to claim 1, wherein the weight average molecular weight of the acrylic polymer (A) is 300,000 to 1,000,000.

4. 2. The adhesive composition for application to skin according to claim 1, characterized in that the carboxyl group-containing monomer constituting the acrylic polymer (A) contains methacrylic acid and further contains either acrylic acid or 2-carboxyethyl acrylate.

5. An adhesive tape for application to the skin, comprising a substrate and an adhesive layer formed from the adhesive composition for application to the skin according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Pressure-sensitive adhesive suitable for skin and method of preparing the same

    JP2009062543A

  • Adhesive and adhesive tape

    JP2017095598A